Newer initiatives in revised national tuberculosis control programme and its current implementation status - Soyam, Vishal; Boro, Pallavi (Asian Journal of Medical Sciences, 2015)
The Revised National Tuberculosis Control programme has continuously innovative and progressive in addressing issues related to Tuberculosis control in India. With the implementation of RNTCP, India has taken huge stride in reduction of mortality and morbidity due to TB. The programme has actively incorporated various new ideas, innovations and information communication technology to curb this menace. These newer initiatives provide unprecedented opportunities to control Tuberculosis more efficiently if it implemented effectively. India has made enormous progress towards TB control through their honest effort. Innovations will effectively leverage India’s endeavour. Programme must continue and sustain these efforts to make India TB free. DOI: http://dx.doi.org/10.3126/ajms.v6i5.11945 Asian Journal of Medical Sciences Vol.6(5) 2015 1-8